Asymmetric Adaptability: Dynamic Team Structures as One-Way Streets - Moon, Henry; Hollenbeck, John R.; Humphrey, Stephen E.; Ilgen, Daniel R.; West, Bradley J.; Ellis, Aleksander P. J.; Porter, Christopher O. L. H. (Academy of Management Journal, 2004)
This study tested whether teams working on a command and control simulation adapted to structural change in the manner implied by contingency theories. Teams shifting from a functional to a divisional structure showed better performance than teams making a divisional-to-functional shift. Team levels of coordination mediated this difference, and team levels of cognitive ability moderated it. We argue that the static logic behind many contingency theories should be complemented with a dynamic logic challenging the assumption of symmetrical adaptation.